2021
DOI: 10.1007/jhep05(2021)230
|View full text |Cite
|
Sign up to set email alerts
|

Jet wake from linearized hydrodynamics

Abstract: We explore how to improve the hybrid model description of the particles originating from the wake that a jet produced in a heavy ion collision leaves in the droplet of quark-gluon plasma (QGP) through which it propagates, using linearized hydrodynamics on a background Bjorken flow. Jet energy and momentum loss described by the hybrid model become currents sourcing linearized hydrodynamics. By solving the linearized hydrodynamic equations numerically, we investigate the development of the wake in the dynamicall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 135 publications
0
18
0
Order By: Relevance
“…In this proceedings, we review the power of our novel deep learning techniques to locate with precision the jet creation point in the transverse plane, by selecting jets according to jet energy loss 𝜒, width 𝑅 𝑔 and orientation, which constitutes a significant step towards the exploitation of tomographic power of energetic jets. In future work, the tomographic power is expected to be further improved by considering the interplay between the jet and the local properties of the medium, e.g., the local hydrodynamic flow [23,24,[37][38][39] or spatial-temporal gradients [21,22,24], which determine preferred directions and deformed radiation spectra for the soft emissions from the jet. A direct extraction of the traversed length 𝐿 of energetic jets in the QGP is highly desirable to push forward this series of studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this proceedings, we review the power of our novel deep learning techniques to locate with precision the jet creation point in the transverse plane, by selecting jets according to jet energy loss 𝜒, width 𝑅 𝑔 and orientation, which constitutes a significant step towards the exploitation of tomographic power of energetic jets. In future work, the tomographic power is expected to be further improved by considering the interplay between the jet and the local properties of the medium, e.g., the local hydrodynamic flow [23,24,[37][38][39] or spatial-temporal gradients [21,22,24], which determine preferred directions and deformed radiation spectra for the soft emissions from the jet. A direct extraction of the traversed length 𝐿 of energetic jets in the QGP is highly desirable to push forward this series of studies.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to do so will result in a subsample of jets produced in PbPb that only includes jets that have experienced significant modification making the assessment of modifications, at observable level, clearer. A recent study [16] showed that a convolutional neural network (CNN) trained on jet images for jets modified using the strong/weak Hybrid model [17] including effects of medium response [18] allowed for the extraction, on a jetby-jet basis, of the p T the jet would have had if no QGP was present. These important results rely, at least in significant part, on the presence of a medium response component which is the leading feature identified by the CNN as signalling the strength of quenching effects.…”
Section: Jhep11(2021)219mentioning
confidence: 99%
“…These important results rely, at least in significant part, on the presence of a medium response component which is the leading feature identified by the CNN as signalling the strength of quenching effects. However, the medium response remains the most model-dependent component of state-of-the-art [18][19][20] jet quenching simulations and is not inconceivable that features highlighted by the CNN may be model-specific and absent in real data.…”
Section: Jhep11(2021)219mentioning
confidence: 99%
“…Jets that develop while immersed in a hot background medium have modified structure relative to those formed in vacuum, for example due to medium-induced emission [13][14][15][16] or drag [17][18][19][20][21][22]. In addition, partons in the jet excite a "wake" in the medium they pass through [23][24][25][26][27][28][29]. This wake carries momentum in the jet direction "lost" by the jet partons and after hadronization therefore yields lower-p T particles from the medium that are correlated with the jet direction.…”
Section: Introductionmentioning
confidence: 99%